Analysis of Coffee Product Packaging Development Based on Consumer Preferences Using the Quality Function Deployment (QFD) Method of Budi UMKM in Luwu Regency - Putri, Mirnawati; Mail, Abdul; Rauf, Nurhayati (Omnia Tempus, 2022)
Purpose: The purpose of this study is to find out what attributes are the needs of consumers in the development of coffee product packaging. Attributes are the needs of consumers in the development of coffee product packaging. Design/methodology/approach: This study uses the Quality Function Deployment (QFD) method to analyse the Development of Budi's MSME Coffee Packaging Products in Luwu Regency Based on Consumer Preferences. Findings: The result of this study is the attributes that are the needs of consumers in the development of coffee product packaging, namely there are 12 attributes, which must be fulfilled in producing quality coffee product packaging, the resulting packaging product is a standing pouch-shaped packaging that uses a combination of cream and brown colours, packaging label design in the form of stickers and packaging sizes vary. The brand position and logo are placed on the front of the packaging and product information on the back of the packaging. Research limitations/implications: Respondents in this study were consumers who consumed coffee products. The implementation stage of QFD only reached product packaging planning (house of quality), packaging costs were not discussed in this study and did not involve costs in this study. Originality/value: Coffee is one of the plantation crops that has long been cultivated in Indonesia and holds an important part for the national economy as one of the export commodities. So packaging becomes very important because it becomes an interagency with consumers, therefore the packaging must be able to provide a spontaneous impression that affects the positive actions of consumers at the point of sale. The packaging used in UMKM Budi still uses ordinary plastics that are still not in demand by consumers and coffee product packaging does not have clear information about products so it is less marketable and difficult to compete in the market.